2017
DOI: 10.1007/s10690-017-9225-2
|View full text |Cite
|
Sign up to set email alerts
|

Weather Effects on Stock Returns and Volatility in South Asian Markets

Abstract: We study the effect of mood-proxy variables on index returns and volatility in six South Asian markets. Our mood-proxy variables include six weather (temperature, humidity, cloud cover, air pressure, visibility, and wind speed)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 40 publications
(22 reference statements)
1
7
0
Order By: Relevance
“…Fourth, La Porta et al (2000) suggest that resources may be diverted before earnings are reported, resulting in an overestimated dividend to earnings ratio. Finally, the intense volatile nature of stock markets in Asian countries particularly in Pakistan (Sheikh et al , 2017) may increase the possibility of unstable dividend to market capitalization ratio. Thus, to avoid any potential difficulties, we scale dividends by total assets.…”
Section: Methodsmentioning
confidence: 99%
“…Fourth, La Porta et al (2000) suggest that resources may be diverted before earnings are reported, resulting in an overestimated dividend to earnings ratio. Finally, the intense volatile nature of stock markets in Asian countries particularly in Pakistan (Sheikh et al , 2017) may increase the possibility of unstable dividend to market capitalization ratio. Thus, to avoid any potential difficulties, we scale dividends by total assets.…”
Section: Methodsmentioning
confidence: 99%
“…Having scrutinized data from several major equity markets (Australia, Canada, Germany, Japan, Sweden, Taiwan, UK and the United States), Cao and Wei (2005a) find evidence that supports their theoretical conjectures: when the temperature is high (low), apathy dominates aggression (aggression dominates apathy); this, in turn, impedes (increases) risk-taking and results in lower (higher) stock returns. Other studies demonstrate a similar pattern within numerous developed and emerging stock markets around the world (Cao & Wei, 2005b;Chang et al, 2006;He & Ma, 2021;Hou et al, 2019;Sheikh et al, 2017;Yoon & Kang, 2009). Although several controversies emerged with concerns about the behavioral mechanism behind this phenomenon (see, e.g., Jacobsen & Marquering, 2008Kamstra et al, 2009), the overall conclusion appears unequivocal: A higher temperature coincides with lower stock returns (and vice versa).…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 72%
“…The literature has documented few latest investigations which takes evidence from Sri Lanka. Sheikh et al (2017) examined the effect of six weather mood-proxy variables (temperature, humidity, cloud cover, air pressure, visibility and wind speed), three weather indicators (fog, thunder storm and rain or drizzle) and two biorhythmic variables on index return volatility in six South Asian markets in four countries, namely, Sri Lanka, India, Pakistan and Bangladesh. The findings of the study suggested that mood-proxy variables have influences in South Asian capital markets.…”
Section: Weather and Equity Returnsmentioning
confidence: 99%